STRATEGI MANAJEMEN ADMINISTRASI DALAM MENGATASI KENDALA PEMBERKASAN TUNJANGAN PROFESI GURU PAI KEMENTERIAN AGAMA MANDAILING NATAL - Indah Herawati Gea; Ummu Hanifah; Marlina Marlina; Khodma Siah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The Teacher Professional Allowance (TPG) is an important government initiative aimed at improving the living conditions and professionalism of teachers. However, in its implementation, the processing of TPG documents still faces numerous administrative issues, particularly in work units such as the Islamic Religious Education Section.. This study aims to examine administrative management methods in addressing issues related to the Teacher Professional Allowance (TPG) documents within the Islamic Religious Education Section. The study employs a qualitative method with a descriptive study type. Data were obtained through in-depth interviews, observations, and document analysis of the staff in the Islamic Religious Education Section and teachers who receive the TPG. The data were analyzed interactively by filtering data, presenting information, and drawing conclusions, while ensuring data accuracy through source and method triangulation. The research results show that the administration management of TPG files has been carried out in accordance with existing regulations, but it is still not optimal. The main issues include document discrepancies, lack of workforce, low administrative understanding among some teachers, and ongoing regulatory changes. To address these issues, the Islamic Religious Education Section implements administrative management approaches such as enhancing internal coordination, strengthening communication and providing guidance to teachers, flexibility in task allocation, and utilizing digital administration systems.